Management of Infected Total Knee Arthroplasty by a New Innovative Customized Articulating Knee Spacer: An Early Experience - Marothi, Dhiraj P (J Orthop Case Rep, 2016)
INTRODUCTION: Management of infected total knee arthroplasty (TKA) is a challenge to patient and surgeon alike. Two-stage exchange is the universally acclaimed method to tackle this problem. Various spacer devices are available for the first stage surgery for local delivery of antibiotics. Here, we report our experience with management of infected TKA patients with our indigenously designed and produced knee spacer. CASE REPORT: Between 2012 and 2013, 28 patients with infected total knee replacement (TKR) have been managed by our indigenous knee spacer. Minimal spacer-related complications and a stable knee joint with range of motion up to 100° were noted in these patients. After a mean period of 6-8 weeks, the spacer was removed and definitive TKR fixation done. At a mean follow-up of 4-months post second stage definitive surgery, patients were infection free with no evidence of recurrence of infection. CONCLUSION: Our new innovative customized articulating knee spacer, which has intramedullary stem extension, has potential to significantly reduce spacer-related complications along with providing improved knee function.